2017
DOI: 10.2527/jas2017.1596
|View full text |Cite
|
Sign up to set email alerts
|

Variance components for direct and maternal effects on body weights of Katahdin lambs

Abstract: The aim of this study was to estimate genetic parameters for BW in Katahdin lambs. Six animal models were used to study direct and maternal effects on birth weight (BWT), weaning weight (WWT), and postweaning weight (PWWT) using 41,066 BWT, 33,980 WWT, and 22,793 PWWT records collected over 17 yr in 100 flocks. Models included fixed effects of management group, dam age, type of birth (for BWT) or birth and rearing (for WWT and PWWT), and lamb age at weighing (fitted as a covariate for WWT and PWWT; all < 0.05)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 21 publications
3
13
4
Order By: Relevance
“…Neither the univariate direct variance and heritability or the univariate maternal variance and heritability in this study show a specific trend, which is not in line with most reported results. In most flocks, direct variance and heritability increase with age from weaning onwards, while maternal variance and heritability decrease with an increase in age (Snyman et al, 1995;Vaez Torshizi et al, 1996;Ngere et al, 2017). However, the univariate phenotypic variance in this study did show an increase with age of the animal.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…Neither the univariate direct variance and heritability or the univariate maternal variance and heritability in this study show a specific trend, which is not in line with most reported results. In most flocks, direct variance and heritability increase with age from weaning onwards, while maternal variance and heritability decrease with an increase in age (Snyman et al, 1995;Vaez Torshizi et al, 1996;Ngere et al, 2017). However, the univariate phenotypic variance in this study did show an increase with age of the animal.…”
Section: Discussioncontrasting
confidence: 49%
“…Growth is regarded as one of the most important traits for the selection of replacement animals in both wool and mutton sheep enterprises (Snyman & Cloete, 2008), as the growth rate and body weight of lambs at different ages determine the profitability of the enterprise (Mohammadi et al, 2013;Ngere et al, 2017). Body weight is positively correlated with many other traits of economic importance, such as reproduction (Safari et al, 2007b;Olivier & Cloete, 2011;Olivier, 2014), adaptability (Singh et al, 2016), wool production (Baneh et al, 2013;Olivier, 2014) and survival at birth (Baneh et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For body weight, we demonstrated that maternal genetic and permanent environmental effects should be simultaneously considered in the model, assuming the direct‐maternal genetic covariance zero. Similarly, it was found that maternal effects play an important role in body weight of pig (Alves et al., 2018), cattle (Aziz et al., 2005; Swalve, 1993), sheep (Kumar et al., 2017; Mohammadi et al., 2013; Ngere et al., 2017; Ulutas et al., 2013), turkey bird (Aslam et al., 2011), Japanese quail (Lotfi et al., 2012) and chicken (Hartmann et al., 2003; Koerhuis & Thompson, 1997; Tongsiri et al., 2019; Tosh et al., 2010). For shank length, shank girth and feather maturity, the best model (model 3) considered maternal genetic effect with the direct‐maternal genetic covariance zero.…”
Section: Discussionmentioning
confidence: 94%
“…In small ruminant production systems, adaptation to environmental conditions, such as heat tolerance and the ability to survive numerous endemic disease challenges is considered a critical factor (Bishop, 2012). With increasing demand for sheep in Brazil's Southeast region, https://doi.org/10.1016/j.smallrumres.2018.07.003 Received 10 February 2018; Received in revised form 10 July 2018; Accepted 11 July 2018 T methods to control of GINs have been studied, and the use of more resistant breeds is considered a viable alternative (Mugambi et al, 1997;Rocha et al, 2005;Amarante et al, 2009;McManus et al, 2009;Ngere et al, 2017). Analysis of faecal egg counts (FEC) has been used in many experiments to characterize the resistance to GINs of small ruminants, finding heritability levels ranging from 0.01 to 0.65 (Zvinorova et al, 2016).…”
Section: Introductionmentioning
confidence: 99%